New trends in personal names among pentecostals in south western Nigeria (2016)
Research attention has been devoted to personal names in different cultures all over the world. However, there is an emerging trend among the Pentecostals, which to the best of our knowledge has not been explored. This is the tendency to place more emphasis on how names sound, rather than the meanings of such names. This paper is devoted to this issue. Data were elicited from 20 parents (15 mothers and 5 fathers); overall 60 children with different names are reflected in the data. Halliday’s Systemic Functional Theory (SFT) formed the theoretical background of the paper. Here, the emphasis is on the function and use which the user of language makes it to perform. In this case, the aesthetic function has an over-riding precedence over other functions, such as religion, harmony with fathers' names, and family backgrounds. Even though, all these are reflected in the names examined, but the sound component is more pervasive than any other. The morphological analysis of the names also reflects that four morphological processes are involved. These are Prefixation, Alphabetism, Clipping and Composition. There is a subtle revolution in naming practices being precipitated/initiated by Pentecostal parents